2011
DOI: 10.1155/2011/792639
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinases and Reactive Oxygen Species: How Can ROS Activate MAPK Pathways?

Abstract: Mitogen-activated protein kinases (MAPKs) are serine-threonine protein kinases that play the major role in signal transduction from the cell surface to the nucleus. MAPKs, which consist of growth factor-regulated extracellular signal-related kinases (ERKs), and the stress-activated MAPKs, c-jun NH2-terminal kinases (JNKs) and p38 MAPKs, are part of a three-kinase signaling module composed of the MAPK, an MAPK kinase (MAP2K) and an MAPK kinase (MAP3K). MAP3Ks phosphorylate MAP2Ks, which in turn activate MAPKs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
603
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 910 publications
(664 citation statements)
references
References 37 publications
21
603
0
6
Order By: Relevance
“…As indicated, Kss1/Fus3-encoded yeast MAPK is closely related to mammalian ERK-type kinases, which functions as a critical checkpoint for protein biosynthesis [34,35]. In other words, if MAPK is inactivated, protein biosynthesis should be suppressed [36]. After exposure of PME yeast cells to CR, ART, or H 2 O 2 , downregulation of MAPK pathway genes and ribosomal protein genes occurs, implying protein biosynthesis is hampered in PME yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated, Kss1/Fus3-encoded yeast MAPK is closely related to mammalian ERK-type kinases, which functions as a critical checkpoint for protein biosynthesis [34,35]. In other words, if MAPK is inactivated, protein biosynthesis should be suppressed [36]. After exposure of PME yeast cells to CR, ART, or H 2 O 2 , downregulation of MAPK pathway genes and ribosomal protein genes occurs, implying protein biosynthesis is hampered in PME yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since intracellular ROS activate the mitogen-activated protein kinase (MAPK) pathway in the mediation of STZ-induced cell death [24,25] , we next investigated whether LX2343 has a regulatory effect on the MAPK pathway. The results demonstrated that incubating SH-SY5Y and primary neuronal cells with STZ for 4 h induced an ~2.5-fold increase in JNK and p38 phosphorylation compared with the controls (Figure 3A), whereas LX2343 treatment antagonized the STZ-induced increase in phosphorylated JNK, c-Jun, and p38 in both SH-SY5Y ( Figure 3B, 3C) and primary neuronal cells ( Figure 3D, 3E) but had no effects on ERK ( Figure 3A and 3F) or p53 (Figure 3F) in SH-SY5Y cells.…”
Section: Lx2343 Inhibited Jnk/p38 Signalingmentioning
confidence: 99%
“…In addition, several studies have demonstrated that ROS can induce activation of MAP kinases, including ERK (29,30). Because both poly I:C and CpG are known inducers of ROS (31, 32), we tested the possibility that ERK was phosphorylated via a ROS-dependent mechanism in BMDMs stimulated with these ligands.…”
Section: Tlr3 and 9 Activate Erk Indirectly Via Nadph-oxidase-dependentmentioning
confidence: 99%